PENGARUH KUALITAS REGULASI TERHADAP INVESTASI ASING DI INDONESIA DENGAN PENDEKATAN VECTOR ERROR CORRECTION MODEL (VECM) PERIODE 2002–2022 - Wira Ganet Aribowo; Mutmainah; Fergiawan Alfianto Rizkaputra (Universitas Merdeka Madiun, 2025)
This study investigates the dynamic relationship between the Regulatory Quality Index (RQI), Foreign Direct Investment (FDI), Gross Domestic Product (GDP), and Bank Capital to Assets Ratio (BCAR) in Indonesia from 2002 to 2022, utilizing the Vector Error Correction Model (VECM) approach. The model captures both short-term dynamics and long-term equilibrium relationships among the variables. The results reveal that all variables are integrated of order one (I(1)) and share a cointegrating relationship, supporting the use of VECM. Empirical findings indicate that GDP has a significant and positive impact on regulatory quality in both the short and long run. FDI exerts a limited positive effect, while BCAR does not have a significant short-term influence on RQI. The statistically significant error correction term (ECT) confirms the existence of an adjustment mechanism toward long-run equilibrium. These findings highlight the crucial role of economic growth, foreign investment, and financial system stability in enhancing regulatory and institutional quality in Indonesia.